To heal and take care: medical micropigmentation and its role in improving body image - Santi, Pier Luigi; Franchelli, Simonetta; De Paoli, Francesca; Pesce, Marianna; Vachtsenovanos, Sofia; Rubino, Luca; Parodi, Aurora; Friedman, Daniele (Medicina Historica, 2023)
The practice of tattooing dates back to a remote past and is characterised by its many different purposes. However, in the last decades, such practice has become a cultural phenomenon, extending its reach to a broader population, including adolescents. More recently, in the perspective of enhancing a broader therapeutic approach, heedful of the many different needs of the individual, the practice of micropigmentation has become widespread in the medical field in order to offer the possibility of reconstructing the body image where skin, pathological manifestations, and congenital or acquired imperfections, have altered its physiological appearance with a non-invasive methodology. Its application indicates a commitment to a more humane form of treatment based on a multidimensional approach to the person and on integrating different skills and expertise, not only from the medical arena but also from the technological one. However, the practice of dermal pigmentation presents risks that require adequate professional training and broad communication between practitioner and patient to assess the existence of ideal conditions for its implementation carefully.